CLINICAL AND CT SCAN FEATURES OF COVID-19 PATIENTS ADMITTED TO THE CENTER FOR VIROLOGY, INFECTIONS AND TROPICAL DISEASES ABOUT 186 CASES - MOUTMIR Yasmine (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2021)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, responsible of the pandemic that is currently raging on, and that initially emerged in China in December 2019. It represents, not only a major threat to global public health, but also a huge economic burden and panic to society. Around 80% of the infected subjects will experience only mild to moderate symptoms. However, in 10 to 20% of cases, the clinical presentation happens to be much more critical, requiring specific management, mainly in elderly subjects and those with associated comorbidities. Our work, which aimed to describe the clinical, biological and morphological presentation of the first COVID-19 cases, to establish a possible correlation between the clinical and morphological features on CT scan, and to define the predictive factors of an unfavorable outcome, focused on a retrospective descriptive and analytical study about 186 cases from March through June 2020. Our study showed predominance in the age group between 25 and 39 years old, with a median age of 34 years old, as well as a higher prevalence among males (90.9%) compared to females (9.1%) with a sex ratio of 9.94. 10.8% had comorbidities, with hypertension being the most common comorbidity, followed by asthma, diabetes and heart disease. 45.2% of the patients were asymptomatic, and 53.2% had normal a CT scan. And our study found out a significant correlation between clinical and CT scan data, as asymptomatic patients are more likely to present with normal CT scan findings. All our patients recovered and were discharged, and no deaths were reported.
Keywords: COVID-19; aspects cliniques; aspects morphologiques; clinical features; CT scan features